Family Planning Midwifery Care For Mrs. "Y" A Combined Oral Contraceptive User With Headache Complaints At Wolio Health Center - Yuyun; Siti Aisyah Ansi; LM. Zainal Abidin K (International Journal of Multidisciplinary Learners, 2024)
Background: Contraception is a method to prevent pregnancy that occurs due to the meeting of a mature egg and sperm. Oral contraception contains hormones, either in the form of a combination of progestin and estrogen hormones or only progestin hormones. The subject of this care is Ms. "Y," a 32-year-old user of the Combined Oral Contraceptive Pill, who was comprehensively treated at Wajo Health Center, Baubau City. Objective: This Final Assignment Report aims to provide midwifery care related to family planning services to Ms. "Y," a user of the Combined Oral Contraceptive Pill, who experienced headaches at Wolio Health Center, Baubau City. Method: This research is a case study using the Varney 7-step management approach and SOAP, which includes basic data collection, basic data interpretation, identification of actual and potential problems, immediate actions, care planning, implementation, and evaluation. Results: From the case study obtained from Mrs. "Y", with complaints of headaches, the general condition of the mother was good, weight 52 kg, vital signs blood pressure 120/70 mmHg, pulse 80 x/min, respiration 20 x/min, temperature 36.5 °C. Conclusion: From this case, it can be concluded that appropriate midwifery care was provided, thus resolving the headache issue.